Taxonomic review of the genus Leucopholis Dejean, 1833 (Coleoptera: Scarabaeidae: Melolonthinae: Leucopholini) in the Philippines - Calcetas, Orlando A.; Adorada, Jessamyn R. (Zootaxa, 2017)
The genus Leucopholis Dejean, 1833 (Coleoptera: Scarabaeidae: Melolonthinae: Leucopholini) is reviewed for the species from the Philippines. Five species of Leucopholis occur in the Philippines, including one new species. Keys to the genera of Leucopholini and to the species of Leucopholis in the Philippines are provided.